Evidence for a Cooperative Mechanism Involving Two Palladium(0) Centers in the Oxidative Addition of Iodoarenes. Issue 9 (17th January 2018) - Perego, Luca Alessandro; Payard, Pierre‐Adrien; Haddou, Baptiste; Ciofini, Ilaria; Grimaud, Laurence
Abstract: Oxidative addition of iodoarenes (ArI) to Pd 0 ligated by 1‐methyl‐1 H ‐imidazole (mim) in polar solvents leads to cationic arylpalladium(II) complexes [ArPd(mim)3 ] + . Kinetic analyses evidence that this reaction is second order with respect to the concentration of Pd 0, and a mechanism involving the cooperative intervention of two Pd 0 centers has been postulated to explain this finding. This unusual behavior is also observed with other nitrogen‐containing ligands and it is general for iodobenzenes substituted with electron‐donating or weakly electron‐withdrawing groups. In contrast, bromoarenes and electron‐poor iodoarenes display first‐order kinetics with respect to Pd 0 . Theoretical calculations performed at the density functional theory (DFT) level suggest the existence of mim‐ligated ArI‐Pd 0 complexes, in which the iodoarene is bound to the metal in a halogen‐bond‐like fashion. Coordination weakens the C−I bond and facilitates the oxidative insertion of another Pd 0 center across this C−I bond. This conceptually novel mechanism, involving the cooperative participation of two distinct metal centers, allows a full explanation of the experimentally observed kinetics. Abstract : A palladium duo : Oxidative addition of iodoarenes to Pd 0 complexes with nitrogen ligands obeys second‐order kinetics with respect to Pd 0, and a mechanism involving the cooperative intervention of two metal centers is proposed to explain this finding (see graphic). Theoretical calculations suggest the existence of ArI−Pd 0 complexes, in which the iodoarene is bound to the metal in a halogen‐bond‐like fashion, thus weakening the C−I bond and facilitating the insertion of another Pd 0 center.